Isolation, solubility and in vitro hydrolysis of chickpea vicilin-like protein - Tavano, Olga Luisa [UNESP]; Neves, Valdir Augusto [UNESP] (Elsevier B.V., 2008)
The chickpea vicilin-like globulin was isolated and chromatographed on Sepharose CL-6B and Sephacryl S-300. The native globulin with a molecular weight of 140 kDa was resolved in Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) in seven polypeptide bands in the range of 12.4-67 kDa. The solubility profile of the protein in water and NaCl solutions was typical of a legume globulin. The purified vicilin-like globulin, native and heated, was hydrolyzed by pepsin, trypsin and chymotrypsin. The hydrolysis patterns indicated that the native vicilin-like protein was only partially degraded by the enzymes in comparison with casein. Heating increased its susceptibility to hydrolysis relative to the native form, for all the enzymes. However, the results obtained by the pH-drop method revealed that the in vitro digestibility of the vicilin-like protein was not altered by heating, while 11 S-like and total globulins suffered a small increase, indicating that the structural characteristics of storage globulins may be important factors limiting the protein digestion. (c) 2007 Swiss Society of Food Science and Technology. Published by Elsevier Ltd. All rights reserved.
Keywords: chickpea; globulins; vicilins; characterization; in vitro hydrolysis